DEVELOPMENT OF E-MODULES USING THE FLIPBOOK BUILDER APPLICATION BASED ON DISCOVERY LEARNING - Reyando Pardosi; Roza Thohiri (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2022)
This research was conducted using the Research and Development (R&D) method. The research and development steps are guided by the ADDIE model (Analyze, Design, Development, Implementation and Evaluation). The development stage has 2 stages, namely 1). Validation test in which there are three validators, namely material experts, media experts and design experts. 2). The practicality test in which there are several stages, namely the test of the tax subject lecturer (one person), the small group test (8 people) and the large group test (30 people). The results of the validation from material experts, media experts and design experts were obtained that the criteria could be used with partial revisions with a result of 85%, could be used with partial revisions with 87.5% results and could be used with partial revisions with 86.1% results. after being given treatment, the value obtained increased by 86% in the range A and B. In the second stage, namely the student response test, the student got a positive score of 90.6% which is where the E-module is very effectively used in the learning process.